The Exegesis of The Parent’s Assessment On The Teachers Teaching Quality According to 2 Timothy 2:15-21 - Hannas Hannas; Rinawaty Rinawaty; Andy Paulus (Theological Journal Kerugma, 2019)
Parents have the potential to doubt the the teacher’s quality in teaching the students, that is why a barometer or indicators are needed so that the teacher as an educator can be assessed objectively. Ideas built by the experts are needed as the best solution as well as biblical principles to find the right formula. This study uses the exegesis method which is seen through contextual analysis, syntactical analysis, verbal analysis, theological analysis and homiletical analysis. This study found what is meant by parents' assessment on the teachers’ teaching quality according to 2 Timothy 2:15-21 is the act of assessing the intelligence, the potential done by the father or the mother regarding good quality or services in facilitating the activities of learning or training through explanations, questions and answers, discussions, and expressing the opinions guided by competent educators or instructors, who are characterized by: teaching professionally (verse 15), teaching correctly in accordance with learning material (paragraph 15), teaching in accordance with learning objectives (verse 16-19), teaching with the right media (verse 20) and teaching with the right method (verse 21).